Possibilities and challenges for cooperative learning in virtual environments (Research, Society and Development, 2023)
Cooperative learning in virtual learning environments is a teaching modality in which students work together to achieve common goals. This work aimed to discuss the possibilities for cooperative learning in virtual teaching models, known as AVA. The methodology used is a literature review where articles published between 2017 and 2022 were used. It was observed that this learning modality is mediated by technologies, such as virtual platforms and videoconferences. Students can work together on collaborative activities and exchange information through discussion forums and other resources available on the virtual platform. Cooperative learning in virtual environments presents possibilities for the development of students' social, intellectual and emotional skills, but it also presents challenges such as lack of face-to-face interaction and difficulty in establishing cooperation. To overcome these challenges, specific tools and strategies, such as discussion forums and collaborative activities, are necessary. The presence of a qualified tutor is also essential. The success of cooperative learning in virtual environments depends on a combination of factors involving technology, the role of the tutor and active participation of students.